Sports medicine for the emergency physician : a practical handbook - Waterbrook, Anna (New York : Cambridge University Press, 2016)
Written by sports-trained emergency physicians Sports Medicine for the Emergency Physician: A Practical Handbook is the only resource of its kind, created specifically for the emergency medicine provider. It is designed to be used as a reference tool, and includes high-yield physical exam skills and key management of sport injuries in the emergency department. Each chapter is dedicated to a specific joint (or joints) and includes the basics of a high-yield physical examination including inspection, palpation, range of motion, special tests, as well as neurovascular and skin exams. Corresponding figures of essential anatomy, pictures of physical exam maneuvers, and clinical correlations are also featured. Emergent and common musculoskeletal conditions for each joint(s) are discussed, as well as the appropriate emergency department management for each condition. Additional chapter topics include sports concussions, sports cardiology, heat illness, and common splints used in the emergency department.
Machine generated contents note: 1. Shoulder Christopher Guyer; 2. Elbow Christopher Hogrefe, Ross Mathiasen and Timothy Thomsen; 3. Wrist Christopher Pruitt; 4. Hand Yvonne Chow and Amanda Akin; 5. Pelvis, hip, and thigh Aaron Monseau and Brenden Balcik; 6. Knee Allison Lane; 7. Lower leg and ankle Christopher Gee; 8. Foot Brenden J. Balcik, Aaron J. Monseau and William Krantz; 9. Cervical spine Matthew Baird; 10. Lumbar spine Jeffrey Feden; 11. Concussion Melissa Leber; 12. Arrhythmias and sudden cardiac arrest in athletes Moira Davenport; 13. Exertional heat illness Brian Springer; 14. Basic principles of splinting in the emergency department Anna L. Waterbrook.
Title from publisher's bibliographic system (viewed on 05 May 2016).
Keywords: Sports emergencies -- Handbooks, manuals, etc; Sports medicine -- Handbooks, manuals, etc; Emergency medicine -- Handbooks, manuals, etc; Physicians -- Handbooks, manuals, etc